Addition of silver nanoparticles has no long‐term effects on natural phytoplankton community dynamics in a boreal lake. Issue 4 (2nd March 2018) - Conine, Andrea L.; Rearick, Daniel C.; Paterson, Michael J.; Xenopoulos, Marguerite A.; Frost, Paul C.
Abstract: Lake phytoplankton communities are dynamic with well‐documented seasonal variability in taxonomic composition and biomass. However, this variability has been largely overlooked when assessing the risk posed to aquatic ecosystems by the antimicrobial agent, silver nanoparticles (AgNPs). Here, we report results from a whole lake AgNP addition study at the IISD‐Experimental Lakes Area that assessed the effects of AgNPs on phytoplankton. Phytoplankton communities were largely unaffected in terms of taxonomy, pigment concentration, and biomass by AgNP additions. These negative toxicological results are due to community changes being more strongly affected by natural processes, such as temperature and dissolved nutrients. We conclude that AgNP exposure at environmentally relevant concentrations for 2 yr did not affect phytoplankton communities in boreal lakes, which emphasizes the importance of incorporating natural variability into analyses that attempt to determine the effect of contaminants on aquatic ecosystems.